Are current physical match performance metrics in elite soccer fit for purpose or is the adoption of an integrated approach needed? - Bradley, P. S.; Ade, J. D. (International Journal of Sports Physiology and Performance, 2018)
Time-motion analysis is a valuable data-collection technique used to quantify the physical match performance of elite soccer players. For over 40 years, researchers have adopted a "traditional" approach when evaluating match demands by simply reporting the distance covered or time spent along a motion continuum of walking through to sprinting. This methodology quantifies physical metrics in isolation without integrating other factors, and this ultimately leads to a 1-dimensional insight into match performance. Thus, this commentary proposes a novel "integrated" approach that focuses on a sensitive physical metric such as high-intensity running but contextualizes this in relation to key tactical activities for each position and collectively for the team. In the example presented, the integrated model clearly unveils the unique high-intensity profile that exists due to distinct tactical roles, rather than 1-dimensional "blind" distances produced by traditional models. Intuitively, this innovative concept may aid coaches` understanding of the physical performance in relation to the tactical roles and instructions given to the players. In addition, it will enable practitioners to effectively translate match metrics into training and testing protocols. This innovative model may well aid advances in other team sports that incorporate similar intermittent movements with tactical purpose. Evidence of the merits and application of this new concept is needed before the scientific community accepts this model as it may well add complexity to an area that conceivably needs simplicity.